IndiSoste: the CSR and Sustainability Reporting Application Customized for GRUPO SURA, as A Contribution to the Construction of Corporate Citizenship - Torres, M.C. (2013)
The purpose if this dissertation is to answer to the question of: how can multinational companies, such as GRUPO SURA, that aim to be recognized as good corporate citizens, report in the most integrated way its overall CSR and sustainability practices among all of the organization and its subsidiaries? To answer this question, I based my work on Institutional Theory and my internship from June to December of 2012, in GRUPO SURA’s CSR Management in Medellin, Colombia. My main task was to create the first unified/integrated Application of Sustainability Indicators of the company (called IndiSoste), based on the public statement in which GRUPO SURA declares itself as a corporate citizen. Finally, this practical exercise, theoretically underpinned, can be adapted to different contexts and cultures, and could also contribute to other large companies and multinational companies who want to be recognized as good corporate citizens, and are dealing with reporting issues.